Die Luxemburger Mehrsprachigkeit: Ergebnisse einer Volkszählung - Ferring, Dieter; Allegrezza, Serge; Willems, Helmut; Heinz, Andreas; Fehlen, Fernand (transcript, 2016)
Luxembourg – three official languages and a cosmopolitan population. An innovative contribution to the linguistic demography of a globalized, transnational EU metropolis.